Cutaneous protothecosis - case report - Pâmela Craveiro Gomes da Silva; Sabrina Beirão da Costa e Silva; Ricardo Barbosa Lima; Antonio Macedo D'Acri; Omar Lupi; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2013)
Cutaneous protothecosis is a rare infection caused by achlorophyllic algae of the genus Prototheca. The lesions usually occur on exposed areas, related with trauma, in immunocompromised patients. The most common clinical presentation is a vesicobullous and ulcerative lesion with pustules and scabs, simulating bacterial, fungal or herpetic infections or eczema. The diagnosis is determined by agent identification through histopathology, culture and the carbohydrates assimilation test. The finding of morula-like spherules is characteristic of Prototheca sp. Its rarity and non-specific clinical aspect may difficult the disease diagnosis. We report a case of a diabetic patient, in chronic use of systemic corticosteroids, that developed a skin lesion after trauma to the right leg.